2022
DOI: 10.1002/path.5873
|View full text |Cite
|
Sign up to set email alerts
|

Genetic context of oncogenic drivers dictates vascular sarcoma development in aP2‐Cre mice

Abstract: Angiosarcomas are aggressive vascular sarcomas that arise from endothelial cells and have an extremely poor prognosis. Because of the rarity of angiosarcomas, knowledge of molecular drivers and optimized treatment strategies is lacking, highlighting the need for in vivo models to study the disease. Previously, we generated genetically engineered mouse models of angiosarcoma driven by aP2‐Cre‐mediated biallelic loss of Dicer1 or conditional activation of KrasG12D with Cdkn2a loss that histologically and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Studies demonstrated that biallelic Dicer1 deletion can lead to aggressive and metastatic angiosarcoma, even in the absence of additional oncogenic mutations (90). Studies in mice have demonstrated that biallelic loss of Dicer1 predisposes endothelial cells to angiosarcoma formation, highlighting the critical role of DICER1 in maintaining proper miRNA biogenesis (90,91). This finding strengthens the link between miRNA alterations and angiosarcoma development (82).…”
Section: Oncogenicmentioning
confidence: 69%
“…Studies demonstrated that biallelic Dicer1 deletion can lead to aggressive and metastatic angiosarcoma, even in the absence of additional oncogenic mutations (90). Studies in mice have demonstrated that biallelic loss of Dicer1 predisposes endothelial cells to angiosarcoma formation, highlighting the critical role of DICER1 in maintaining proper miRNA biogenesis (90,91). This finding strengthens the link between miRNA alterations and angiosarcoma development (82).…”
Section: Oncogenicmentioning
confidence: 69%
“…3D and Supplementary Table S3). To determine the miR-497 target genes potentially involved in AS, GO was performed on the 72 overlapping genes downregulated in the miR-497 transfected cells and upregulated in aP2-Cre;Dicer1 cKO (AD cKO ) 30 murine AS tumors (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Resources to study AS are limited, therefore developing models to study the disease is crucial for making novel discoveries. We have previously developed mouse models to recapitulate AS, including models driven by oncogenic KRAS and conditional Dicer1 deletion in endothelial cells 29,30,43 . Because Dicer1 is essential for microRNA (miRNA) biogenesis, this suggests that loss of mature miRNAs is responsible for this tumor development, however, other non-canonical Dicer1 could be attributed as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations